Biosynthesis of Titanium Dioxide Nanoparticles and its Efficacy against Tick Rhipicephalus (Boophilus) microplus - Maddikontla, Sowmya; Pattipati, Malakondaiah; Ravipati, Venu; Nagaram , N Vinod Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The purpose of the present study was to evaluate the acaricidal activity of synthesized titanium dioxide nanoparticles using aqueous flower extract of Calotropis gigantea and encapsulated Azadirachta indica, Ricinus communis on synthesized titanium dioxide nanoparticles (TiO2 NPs) against ticks Rhipicephalus (Boophilus) microplus. The titanium dioxide nanoparticles were synthesized by addition of C. gigantea flower extract with titanium sulphate solution and thus synthesized nanoparticles were characterized using DLS (Dynamic Light Scattering) and zeta potential, FT-IR (Fourier transformed infrared spectroscopy) and SEM (Scanning electron microscope). The maximum efficacy was observed for A-TiO2 (A. indica coated TiO2 NPs) with LC50 and LC99 values of 8.264 and 47.097 ppm. Biofabricated TiO2 NPs posses high acaricidal activity and can be used as alternative to chemical acaricides.